In
△
A
B
C
with
A
B
=
c
,
A
C
=
b
and
B
C
=
a
, where
∠
A
=
5
0
∘
and
∠
B
=
1
0
0
∘
, which of the following expressions hold?
1 . a 3 + c 3 = 3 a c 2 2 . a 3 + c 3 = 3 a 2 c 3 . 3 a 3 + c 3 = 3 a c 2 4 . 3 a 3 + c 3 = 3 a 2 c 5 . 3 a 3 + b 3 = 3 a b 2 6 . 3 b c 2 + 3 c 3 = b 3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Out of the box way of looking at the problem. Though since Sin Law is used, the solution is straight forward without going for expanding Sin cube..
S i n L a w : − S i n ( 5 0 ) a = S i n ( 1 0 0 ) b = S i n ( 3 0 ) c . ∴ c = 2 ∗ S i n ( 5 0 ) a . . . . . . . . . ( A ) D i v i d i n g [ 1 . ] b y a 3 a n d s u b s t i t u t i n g f r o m ( A ) , w e g e t L H S = R H S . S o [ 1 . ] i s a s o l u t i o n . A g a i n b = 2 ∗ c ∗ S i n 1 0 0 . . . . . . . . ( B ) D i v i d i n g [ 6 . ] b y c 3 a n d s u b s t i t u t i n g f r o m ( B ) , w e g e t L H S = R H S . S o [ 6 . ] i s a s o l u t i o n . S o 1 a n d 6 a r e t h e s o l u t i o n s .
Problem Loading...
Note Loading...
Set Loading...
First calculate ∠ C , which is simply ∠ C = 1 8 0 ∘ − ∠ A − ∠ B = 3 0 ∘
By Law of Sines on △ A B C we get:
sin 5 0 ∘ a = sin 3 0 ∘ c sin 5 0 ∘ = 2 c a
Now, in the identity of triple angle sin 3 θ = 3 sin θ − 4 sin 3 θ , put θ = 5 0 ∘ and rearrange:
sin 1 5 0 ∘ = 3 sin 5 0 ∘ − 4 sin 3 5 0 ∘ 2 1 = 3 sin 5 0 ∘ − 4 sin 3 5 0 ∘ 1 = 6 sin 5 0 ∘ − 8 sin 3 5 0 ∘ 1 = 6 ( 2 c a ) − 8 ( 2 c a ) 3 1 = c 3 a − c 3 a 3 c 3 = 3 a c 2 − a 3 a 3 + c 3 = 3 a c 2
Similarly, by Law of Sines we get:
sin 1 0 0 ∘ b = sin 3 0 ∘ c sin 8 0 ∘ = 2 c b
Apply again the identity of triple angle, this time with θ = 8 0 ° :
sin 2 4 0 ∘ = 3 sin 8 0 ∘ − 4 sin 3 8 0 ∘ − 2 3 = 3 sin 8 0 ∘ − 4 sin 3 8 0 ∘ − 3 = 6 sin 8 0 ∘ − 8 sin 3 8 0 ∘ − 3 = 6 ( 2 c b ) − 8 ( 2 c b ) 3 − 3 = c 3 b − c 3 b 3 − 3 c 3 = 3 b c 2 − b 3 3 b c 2 + 3 c 3 = b 3